Conceptual Foundation: Balanced Scorecard in the Educational Context (A Study of the Theory Underlying the Instrument's Creation) - Yovita Chandrayanti; Mutoharoh Mutoharoh; Rafika Nur Sugiharti; Eka Aditya Putri Putranti; Teresia Waruwu; Farid Datu AlRasyid; Febrianus Laia (EDUJAVARE: International Journal of Educational Research, 2026)
Digital transformation has encouraged educational institutions to create more comprehensive, flexible, and data-driven performance assessment systems. This article aims to analyze the implementation of the Digital Balanced Scorecard (DBSC) as a school performance assessment model that supports data-driven education management in the digital era. This study uses a literature review method with a conceptual-critical approach to various national and international studies on the Balanced Scorecard, digital transformation in education, and school information management systems. The results of the study indicate that the implementation of the Balanced Scorecard is able to integrate four main perspectives: financial, customer, internal processes, and learning and growth in one measurable and sustainable evaluation system. From a financial perspective, the study shows that approximately 72.5% of schools are able to manage BOS funds effectively through participatory planning, the use of digital applications such as ARKAS, and strengthening internal audits. From a customer perspective, the quality of educational services, school culture, and institutional image have been shown to have a positive influence of 60.7% on the level of parent and student satisfaction. An internal process perspective shows that the integration of e-learning, monitoring dashboards, and technology-based curriculum innovations can improve the effectiveness of teaching and learning activities and the quality of school administrative services. Meanwhile, from a learning and growth perspective, digital-based teacher learning community (Kombel) management has been shown to improve teachers' pedagogical competence by up to 85%. The integration of digital technology through interactive dashboards, e-performance systems, and school management platforms enables direct, clear, and precise monitoring and decision-making. However, the implementation of the DBSC still faces several challenges, such as limited technological infrastructure, low digital literacy skills, organizational cultural resilience, and the risk of managerialism, which can simplify educational complexity into mere numbers.